2014
DOI: 10.1590/1807-1929/agriambi.v18n09p927-933
|View full text |Cite
|
Sign up to set email alerts
|

Óleo de eucalipto e Pisolithus microcarpus no crescimento de bracatinga em solo contaminado por cobre

Abstract: As áreas de mineração de cobre podem apresentar teores elevados disponíveis deste nutriente no solo afetando o desenvolvimento vegetal. O objetivo do trabalho foi avaliar o efeito do óleo essencial de eucalipto na associação ectomicorrizica com o fungo Pisolithus microcarpus em mudas de bracatinga e seu comportamento em solo contaminado por cobre. O experimento foi conduzido em delineamento inteiramente casualizado em arranjo fatorial (4 x 5) sendo quatro formas de inoculação (testemunha, óleo, fungo e óleo + … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
3
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 21 publications
1
3
0
1
Order By: Relevance
“…According to the estimated values, there was a reduction between the control treatment (natural soil) and the 300 mg dose of Cu kg -1 of soil after plant growth, with 17% for the stem diameter, 39.7% for the dry matter of the root part and 43.2% for the specific superficial area. Studies with tree species have shown a reduction in the stem diameter and root system due to elevated contents of Cu(II) in the soil (Dellai et al, 2014;Silva et al, 2014). This high soil Cu content inhibits root growth, being one of the most evident symptoms of Cu(II) toxicity, just like what was observed in this study.…”
Section: Resultssupporting
confidence: 75%
“…According to the estimated values, there was a reduction between the control treatment (natural soil) and the 300 mg dose of Cu kg -1 of soil after plant growth, with 17% for the stem diameter, 39.7% for the dry matter of the root part and 43.2% for the specific superficial area. Studies with tree species have shown a reduction in the stem diameter and root system due to elevated contents of Cu(II) in the soil (Dellai et al, 2014;Silva et al, 2014). This high soil Cu content inhibits root growth, being one of the most evident symptoms of Cu(II) toxicity, just like what was observed in this study.…”
Section: Resultssupporting
confidence: 75%
“…In ectomycorrhizal isolates, the response was quadratic positive, with an increase of 6% when the UFSC-PT116 isolate was inoculated at the Cu dose of 211.50 mg kg -1 of soil. Dellai et al (2014) reported that the stem diameter of the M. scabrella was significantly reduced when inoculated with the UFSC-PT116 fungus, which indicates that the response of this isolate is influenced by the plant species in association. However, for transplanting the seedlings to the field, a minimum neck diameter of 2 mm is recommended (Wendling and Dutra, 2010) and, in this case, all treatments have adequate values at the Cu doses studied.…”
Section: Resultsmentioning
confidence: 98%
“…The use of mycorrhizal fungi may be an alternative to improve plant development in contaminated areas (Dellai et al, 2014). These fungi form symbiotic associations with vascular plants increasing the area explored by the roots through their hyphae in the soil (Brundrett, 2008;Smith and Read, 2008).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Dellai et al(2014) trabalhando com mudas de bracatinga (Mimosa scabrella Benth) também encontraram redução na massa seca da parte aérea em com o aumento de doses de cobre adicionadas no solo.Figura 2. Figura 3.…”
unclassified